Corrigendum: Psychological Pressure in Competitive Environments: Evidence from a Randomized Natural Experiment - Apesteguia, Jose; Palacios-Huerta, Ignacio (American Economic Review, 2011)
Corrigendum: Psychological Pressure in Competitive Environments: Evidence from a Randomized Natural Experiment by Jose Apesteguia and Ignacio Palacios-Huerta. Published in volume 101, issue 4, pages 1636 of American Economic Review, June 2011